KINERJA RUAS JALAN KEMUNING LOA BAKUNG DI KOTA SAMARINDA - FIKRI, MUAMMAR (KURVA S JURNAL MAHASISWA, 2018)
Kemuning Loa bakung in Samarinda City is a road Secondary collectors that connect primary and secondary regions to each other. The conditions of land use found on Kemuning road are dominated by the public market with trading activities etc. Kemuning Road in Samarinda is classified as a class III road category C. When the economy grows and the level of population prosperity will result in an increase in the level of traffic. Traffic resulting from transportation needs from the community, where people will always look for ways that are faster, safer and smoother. Increasing population and the amount of urbanization to urban areas will cause movement and density, so the need for transportation also increases. On this basis, a research was conducted on the performance of the Kemuning road in Samarinda. In the Kemuning Road Performance Analysis, the Indonesia Manual Road Capacity Manual (MKJI'1997), which is explained by Form UR-1 in General and Geometrical forms of road conditions, UR-2 in the form of advanced input data, namely Flow and Composition of Side of Traffic and Obstacles, UR-3 is in the form of analyzing the free flow rate of light vehicles, light vehicle capacity and speed. In the Kemuning Road Performance Analysis study, a peak hour survey was conducted at Jl. Jakarta to Jl. Kemuning and Jl. KH. Mas Mansyur to Kemuning and the survey was conducted from 8:00 to 9:00, 11:00 to 12:00, 16:00 to 17:00. After calculating existing data, in segment I directions Jl. Jakarta - Kemuning is 1404.44 pcu / hour and the service level is at level C, which means the current stable zone, the driver at the limit of choosing speed. Then Segment II Kemuning Segment II KH. Mas Mansyur - Kemuning is 1404.44 junior / hour from standard <2900 pcu / hour. (Table 2.10) and the service level is at the C level, which means the current stable zone, the driver at the speed limit.